EVALUASI PELAKSANAAN KEBIJAKAN PEMERINTAH TENTANG REVITALISASI PASAR KEMBANG KALISARI - Dian Kristina Prianingrum; Priyatno Harsasto (Journal of Politic and Government Studies, 2019)
This research was conducted to explain the efforts of the Semarang City Government in relation to policy evaluation regarding the revitalization of the Kalisari Flower Market. The research on